UPLAND PROGRAM IN INCREASING THE INCOME OF HIGHLAND FARMERS IN PURBALINGGA REGENCY - Bayu Mahendra; Dwi Putriana Nuramanah Kinding; Alfiyyah Dinda Safitri (Journal of Agri Socio Economics and Business, 2022)
Indonesia has various types of plains that can be used to develop the agricultural sector, one of which is the highlands. The area of the highlands in Indonesia is recorded at 144.47 million hectares. Government policies are needed to increase productivity and income of upland farmers. The UPLAND program of the ministry of agriculture is expected to increase the productivity and income of upland farmers in Indonesia. The purpose of this study is to analyze the increase in the income of upland farmers in Purbalingga district. The analysis is carried out by comparing the productivity and income of farmers before the UPLAND program and after the UPLAND program, so that the significance of the increase can be known. The benefit of the results of this research is that it can be used as a reference for the government in designing and implementing programs related to agriculture. The average net income of farmers before joining the UPLAND program was IDR. 817500,- per month. After participating in the UPLAND program, the income of upland farmers can increase up to IDR. 110,000,-. The results of the paired t test analysis showed that the value of Sig. is 0.00 or <0.05, which means that there is a significant increase in income between before and after the UPLAND program. Respondents in this study were upland farmers who participated in the UPLAND program with the same area of land cultivated and agricultural commodities planted. There were 32 upland farmers working on the exact same land and commodities.